Ripples on the surface. Surnames and genes in Sicily and Southern Italy - Alessio Boattini; Stefania Sarno; Ornella Fiorani; Antonella Lisa; Donata Luiselli; Davide Pettener (Taylor & Francis Group, 2018)
Background: Southern Italy and Sicily played a key role in the peopling history of the Mediterranean. While genetic research showed the remarkable homogeneity of these regions, surname-based studies instead suggested low population mobility, hence potential structuring. Aim: In order to better understand these different patterns, this study (1) thoroughly analysed the surname structure of Sicily and Southern Italy and (2) tested its relationships with a wide set of molecular markers. Subjects and methods: Surname data were collected from 1213 municipalities and compared to uniparental and autosomal genetic markers typed in ∼300 individuals from 8-10 populations. Surname analyses were performed using different multivariate methods, while comparisons with genetic data relied on correlation tests. Results: Surnames were clearly structured according to regional geographic patterns, which likely emerged because of recent isolation-by-distance-like population dynamics. In general, genetic markers, hinting at a pervasive homogeneity, did not correlate with surname distribution. However, long autosomal haplotypes (>5 cM) that compared to genotypic (SNPs) data identify more "recent" relatedness, showing a clear association with surname patterns. Conclusion: The apparent contradiction between surname structure and genetic homogeneity was resolved by figuring surnames as recent "ripples" deposited on a vast and ancient homogeneous genetic "surface".